Affective Assessment dari Teori Menuju Penerapannya dalam Pembelajaran - Dwi Setyadi (Jurnal Pendidikan, 2011)
Affective variable is regarded essential in teaching process. The learners’s attitude against learning process, for example, can significantly influence their achievement. Values which students nurture about truth and integrity will be consequently reflected in their daily conducts. Students’ appreciation against anything will affect everything they do. It is then critical for teachers to design affective assessment.Realities shows that very view of teachers have been willing to seriously design the nurturing model of students’ affection in learning. Teachers should realize when their students become awfully depressed against the learning process because of one and other things. Unfortunately, it is veru rarely heard that teachers systematically make a record on the students’ affection.This article discusses some aspects related to students’ affection against the learning process, and then serves practical procedures, step-by-step to make a record on the students affection in relation to values and attitudes which are critical in learning process.